2013
DOI: 10.1088/1009-0630/15/10/16
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Modification of Activated Carbon Fibers for Adsorption of SO2

Abstract: Viscose-based activated carbon fibers (VACFs) were treated by a dielectric-barrier discharge plasma under the feed gas of N2. The surface functional groups of VACFs were modified to improve the adsorption and catalysis capacity for SO2. The surface properties of the untreated and plasma-treated VACFs were diagnosed by SEM, BET, FTIR, and XPS, and the adsorption capacities of VACFs for SO2 were also compared and discussed. The results show that after the plasma treatment, the external surface of VACFs was etche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Che et al. [ 65 ] treated VACFs using a dielectric‐barrier discharge (DBD) N 2 plasma to improve the adsorption capacities of SO 2 by forming strongly alkaline nitrogenated functional groups to adsorb the acidic SO 2 . The best adsorption efficiency was 21% higher than that of the unmodified VACF.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Che et al. [ 65 ] treated VACFs using a dielectric‐barrier discharge (DBD) N 2 plasma to improve the adsorption capacities of SO 2 by forming strongly alkaline nitrogenated functional groups to adsorb the acidic SO 2 . The best adsorption efficiency was 21% higher than that of the unmodified VACF.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Che et al 84 comparing nontreated and treated AC under dielectric discharge observed di®erent bands through FTIR and XPS analysis. The authors suggest adding of new atoms/structures in AC surface.…”
Section: Physical Modi¯cationmentioning
confidence: 99%
“…Some authors have increased adsorption capacity due to treatment compared to virgin activated carbons (CHE et al, 2013;QU et al, 2013). However, other authors reported that electric discharge had a negative impact on adsorption capacity.…”
Section: Methylene Blue Adsorptionmentioning
confidence: 99%
“…Thus, structural modifications are dependent on the methodology of the treatment that is applied to cause modifications. Che et al (2013) …”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation